Wittgenstein's (misunderstood) religious thought - Fronda, Earl Stanley B. (Philosophy of Religion - World Religions, 2010)
Wittgenstein's religious thought is not well understood. And Wittgensteinian philosophy of religion is charged with fideism, religious non-realism, and even crypto-atheism. These charges, however, are borne of misunderstandings that are a result of the critics' being oblivious of apophatic theology. This book is intended to help clear some of those misunderstandings and neutralize the above-mentioned charges. It argues that Wittgenstein's religious thought shares kinship with the thought of apophaticists in Christendom such as the Pseudo-Dionysius and St. Thomas Aquinas. What appear to be fideism, non-realism, or crypto-atheism to the critics appear differently to those who see Wittgensteinian philosophy of religion from the apophaticists' point of view--Wittgenstein's religious point of view.